Agriculture versus climate change – A narrow staple-based rural livelihood of Papua New Guinea is a threat to survival under climate change - Patrick S. Michael (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2020)
This paper presents a synthesis related to the assessment of climate change and its impacts on productivity of staple crops in Papua New Guinea (PNG), paying close attention to the change in population in the next 80 years. As much as the changes in the climatic and environmental factors will affect agriculture, evidence available in the literature show increase in global and local population will put additional pressure on agriculture by competing with available land and other resources that support agricultural productivity. The developing and underdeveloped countries are considered to be largely vulnerable as more than 85% of the people depend on subsistence agriculture for rural livelihood. This synthesis showed more than 60–85% of the rural people in PNG depend on sweet potato, banana, Colocasia taro, and greater yam. Projection of the population showed there will be 22–31 million people by 2100 and will depend on narrow staple-based subsistence agriculture. The population projected means the density will be 42 people per km2, putting more pressure on limited land available. When that happens, PNG will not be prepared to mitigate, be resilient and adapt because of poor infrastructure, no development plans and lack of post-harvest technologies for loss management of the staples, most of which are root and tuber crops.